1989
DOI: 10.1037/0882-7974.4.3.259
|View full text |Cite
|
Sign up to set email alerts
|

Judgments of origin and generation effects: Comparisons between young and elderly adults.

Abstract: In 2 experiments, young and elderly adults were required to both read words, and generate words by completing word fragments. Subjects were then required to recognize those words that had been presented earlier; for those words that they recognized they judged whether the items had initially been presented in read or generate form. Generation effects (better memory for words that were generated as compared with words that were read) of similar magnitude were observed for both young and older adults. The older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
69
1
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 35 publications
(59 reference statements)
12
69
1
1
Order By: Relevance
“…Previous research Rabinowitz, 1989) has shown that subjects are more likely to correctly judge previously generated medium-taxonomic-frequency items as having been generated than they are to correctly judge previously generated high-taxonomic-frequency items. In contrast, taxonomic frequency has little or no effect on the number of correct judgments for items that were initially read.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous research Rabinowitz, 1989) has shown that subjects are more likely to correctly judge previously generated medium-taxonomic-frequency items as having been generated than they are to correctly judge previously generated high-taxonomic-frequency items. In contrast, taxonomic frequency has little or no effect on the number of correct judgments for items that were initially read.…”
Section: Methodsmentioning
confidence: 95%
“…In experiments of this sort, judgments of origin for generated low-taxonomic-frequency items are more accurate than judgments of origin for generated high-taxonomic-frequency items. There is no effect of taxonomic frequency on the accuracy of origin judgments for items that were initially read Rabinowitz, 1989).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…An important goal for further research is to explore the possibility that some form of guided encoding, such as generation tasks (see, e.g., Rabinowitz, 1989), may reduce or eliminate age-related deficits in encoding context-specific information, even for materials that do not strongly invite such encoding.…”
Section: Resultsmentioning
confidence: 99%
“…The relation between source monitoring and old-new recognition performance is important in studies of aging and memory because recognition memory often declines with age (Light, 1991), along with source accuracy (e.g., Gregory, Mergler, Durso, & Zandi, 1988;Guttentag & Hunt, 1988;Mitchell, Hunt, & Schmitt, 1986;Rabinowitz, 1989). A strong case that older adults have particular problems with source memory can be made when source accuracy is impaired in conditions where recognition performance is equivalent for younger and older adults, or where source accuracy and recognition are differentially influenced by the same manipulation, which has been found in several studies of older adults (Brown et al, 1995;G.…”
Section: The Source Monitoring Framework and Agingmentioning
confidence: 99%